Cargo‐Templated Crosslinked Polymer Nanocapsules and Their Biomedical Applications. Issue 4 (1st February 2021) - Zhao, Yu; Li, Qiushi; Chai, Jingshan; Liu, Yang
Abstract : Cargo‐templated crosslinked polymer nanocapsules (CT‐CPNCs) are mainly synthesized by in situ formation of crosslinked polymer shells on the surface of particulate cargoes, such as therapeutic proteins, siRNA/miRNA, liposomes, chitosans, metal‐organic frameworks (MOFs), and inorganic nanoparticles. CT‐CPNCs exhibit many advantages in biomedical applications, including 1) easy preparation and purification procedures, 2) high structural stability to inhibit undesired leakage of cargoes, and 3) high specific surface area for surface modification (e.g., loading of therapeutic agents and conjugation of targeting ligands). Importantly, CT‐CPNCs are designed with stimuli–responsive properties to release their cargoes in response to internal or external stimuli, including acidic pH values, redox potentials, enzymes (e.g., cathepsin B, hyaluronidase, and matrix metalloproteinases), light exposure, and heat. Herein, the design strategies and recent advances in CT‐CPNCs are focused upon and their potential applications are discussed. Furthermore, the advantages, limitations, future opportunities, and challenges of CT‐CPNCs are also discussed. Abstract : Cargo‐templated crosslinked polymer nanocapsules (CT‐CPNCs) are mainly synthesized by in situ formation of crosslinked polymer shells on the surface of particulate cargoes. Herein, the design strategies, synthesis methods, structures, and properties of CT‐CPNCs are summarized. Recent reports on topics from technology development to the biomedical applications of CT‐CPNCs for the diagnosis and treatment of diseases are provided.